Basic Mathematics and Logic: Workbook - Lambrou M.; Lambrou N.; Djumanov A.; Ataev F. (Tashkent: G`afur G`ulom nomidagi nashriyot-matbaa ijodiy uyi, 2015)
This is a workbook for high-school students stadying basic mathematics in the English language. Readers of the book can find a range of problem solving techniques in mathematics and logic as well as interesting facts on the subject.
Inv.: (NP(B/38456,(NP(B/38457s
Adadi: 500 nusxa